2000
DOI: 10.1161/01.atv.20.5.1257
|View full text |Cite
|
Sign up to set email alerts
|

Assay for Human Matrix Gla Protein in Serum

Abstract: Abstract-Matrix Gla protein (MGP) is synthesized in a vitamin K-dependent way in smooth muscle cells of the healthy vessel wall, and its mRNA transcription is substantially upregulated in atherosclerotic lesions. Here we report the preparation of a monoclonal antibody against human MGP and its use in an enzyme-linked immunosorbent assay. The intra-assay and interassay coefficients of variation in serum samples were 5.4% and 12.6%, respectively, and the lower detection limit was 8.5% of the normal serum value. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 21 publications
5
29
0
1
Order By: Relevance
“…Furthermore, Braam et al found that levels of circulating MGP in patients with type 1 Diabetes Mellitus (which is a risk factor for atherosclerosis) were elevated [40]. Our findings concerning the group B of patients (CKD patients without diabetes) are in agreement with the results of Jono et al, which detected a reverse association between the levels of serum MGP and coronary artery calcification [9].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Braam et al found that levels of circulating MGP in patients with type 1 Diabetes Mellitus (which is a risk factor for atherosclerosis) were elevated [40]. Our findings concerning the group B of patients (CKD patients without diabetes) are in agreement with the results of Jono et al, which detected a reverse association between the levels of serum MGP and coronary artery calcification [9].…”
Section: Discussionsupporting
confidence: 92%
“…26 In patients with severe atherosclelosis, circulating osteocalcin levels were increased. 27 Another study showed that during atherogenesis, osteocalcin had a regulatory role not only in atherosclerotic calcium but also in osteoclastogenesis. 28 Although osteocalcin might be one of the important factors explaining the relationship between endothelial function and bone mass, the present study found that brachial arterial FMD showed no significant association with osteocalcin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…After blotting, membranes were incubated at 4°C overnight with biotin-conjugated a3-15 MGP IgG or a rabbit polyclonal antibody raised against bovine fetuin (23,24). Visualization was via streptavidin-horseradish peroxidase (Amersham Pharmacia, Uppsala, Sweden) and development with ECL Western blotting detection reagents (Amersham Pharmacia).…”
Section: Western Blot Analysismentioning
confidence: 99%